Penyuluhan Kesehatan Reproduksi Pada Remaja Putri Di SMP Negeri 2 Sibulue Desa Sumpang Minangae Kabupaten Bone - Asrianti Safitri Muchtar; Ita Novianti; Sitti Fatimah; Desi Heriyana (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Adolescent reproductive health is a healthy condition originating from the systems, functions and processes of the reproductive organs of adolescents, namely men and women aged 10-19 years and who are not yet married. Teenagers' lack of knowledge about reproductive health will certainly have an impact on attitudes that don't care about their reproductive health. Adolescents experience various problems related to reproductive health such as unwanted pregnancies (KTD), sexually transmitted diseases (STDs) including Human Immunodeficiency Virus (HIV) infection, this is due, in part, to a lack of knowledge and caring attitude towards their reproductive health. The aim of this community service is to provide counseling related to reproductive health to adolescents and then evaluate their level of knowledge before and after the counseling is carried out. The stages are in the form of a pre-test, followed by a presentation of counseling material using the lecture method, followed by a question and answer session and discussion then ending with a participant post-test. The results showed that there was an increase in the level of knowledge of adolescents about reproductive health after the counseling was carried out.